The Effect of Fermentation Feed Combination with Commercial Feed on Growth of Super Native Chicken - H. Husnaeni; J. Junaedi; Wahyu Ningsi (Chalaza Journal of Animal Husbandry, 2019)
This study was aimed to determine the effect of providing a combination of tofu dregs fermentation with commercial feed on the growth of super native chickens. The research was being conducted in June-September 2019 at the Integrated Laboratory of the Faculty of Agriculture, Fisheries and Animal Husbandry, University of Sembilanbelas November Kolaka. The materials were used in this study were super native chicken, fermented feed, and commercial feed (Malindo). The fermented feed consists of tofu dregs, yellow corn, fine rice bran, starch, molasses. Tools that used were digital scales, pans, tarpaulins, cages, feed containers, drinking containers, cables, lamps, sacks, plastic polybags, sacks, feed grinding machines, gas, hoses, buckets, basins. This research was conducted using a Completely Randomized Design (CRD) 4 treatments three replications with each test consisting of 8 super native chickens. The parameters observed were Weekly Consumption, Weekly Body Weight Gain (WBWG), and Feed Conversion. The results showed that the influence of feed consumption was not significant (P 0.05), while the WBWG and Feed Conversion were significantly different due to treatment. So it can be concluded that the use of a combination of fermented tofu pulp and commercial feed with a ratio of 60% and 40% can increase weekly body weight gain and decrease feed conversion so that the use of feed is more efficient